2013
DOI: 10.1007/s00417-013-2323-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-year results of combined intravitreal ranibizumab and photodynamic therapy for polypoidal choroidal vasculopathy

Abstract: Combined intravitreal ranibizumab and PDT was significantly more effective in maintaining and improving VA for PCV patients compared with PDT monotherapy over 24 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Administered therapies appear to be more effective in treatment-naive cases 18 and cases with stage II lesions; both observed decrease in recurrences (16,20). In addition to the anatomically successful outcomes with anti-VEGF monotherapy noted by Arias et al (16) and in the present study, there are also findings indicating that PDT combined with anti-VEGF, triamcinolone, and other modalities were superior to anti-VEGF monotherapy (17)(18)(19).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Administered therapies appear to be more effective in treatment-naive cases 18 and cases with stage II lesions; both observed decrease in recurrences (16,20). In addition to the anatomically successful outcomes with anti-VEGF monotherapy noted by Arias et al (16) and in the present study, there are also findings indicating that PDT combined with anti-VEGF, triamcinolone, and other modalities were superior to anti-VEGF monotherapy (17)(18)(19).…”
Section: Discussionsupporting
confidence: 62%
“…This result differs from the results reported by Arias et al and the present study, but both of those studies included patients who had previously received AMD treatment, unlike the study of Rouvas et al, which enrolled treatment-naive patients. In a case report review presented by Saito et al, (18) increase was reported in the combined treatment group. Nakano et al (19) reported similar results to Rouvas et al, indicating a better increase in BCVA and decrease in CMT for PDT combined with subtenon triamcinolone than PDT monotherapy and combined PDT+anti-VEGF.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…PDT combined with anti-VEGF therapy is currently recommended for treatment of PCV and was reported to have good visual outcome in patients suffering from PCV. [22][23][24][25] However, relatively few studies have investigated the visual prognostic factors following PCV treatments, [26][27][28][29][30] especially the predictive factors following combined therapy. Some of the clinical factors such as age, baseline best-corrected visual acuity and size of haemorrhage, and presence of PED were reported to govern the final visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Combination anti-VEGF and photodynamic therapy (PDT) has been evaluated in both Asian [15][16][17][18][19] and White 20 patients with PCV, with no clear consensus on the superiority of PDT or combination therapy. Most of these studies were conducted in predominantly Asian populations.…”
Section: Introductionmentioning
confidence: 99%